2017
DOI: 10.1523/eneuro.0250-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Monkey Model of the Polyglutamine Diseases Recapitulating Progressive Neurological Symptoms

Abstract: Age-associated neurodegenerative diseases, such as Alzheimer’s disease, Parkinson’s disease, and the polyglutamine (polyQ) diseases, are becoming prevalent as a consequence of elongation of the human lifespan. Although various rodent models have been developed to study and overcome these diseases, they have limitations in their translational research utility owing to differences from humans in brain structure and function and in drug metabolism. Here, we generated a transgenic marmoset model of the polyQ disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
64
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 37 publications
(48 reference statements)
1
64
0
Order By: Relevance
“…This was the first report on the establishment of gene‐modified lines of primates. More recently, the use of transgenic technology in marmosets enabled the generation of a monkey model for human polyglutamine disease, which recapitulated progressive neurological symptoms as found in human patients (Tomioka et al, ). Genetic deletions mediated by genome editing have also become possible in marmosets, and knockout marmoset strains deficient for the interleukin‐2 receptor subunit gamma were generated (Sato et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This was the first report on the establishment of gene‐modified lines of primates. More recently, the use of transgenic technology in marmosets enabled the generation of a monkey model for human polyglutamine disease, which recapitulated progressive neurological symptoms as found in human patients (Tomioka et al, ). Genetic deletions mediated by genome editing have also become possible in marmosets, and knockout marmoset strains deficient for the interleukin‐2 receptor subunit gamma were generated (Sato et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…After the initial technical breakthrough in making GFP-expressing transgenic marmosets (Sasaki et al, 2009), we reported marmosets expressing functional reporter genes (Park et al, 2016), while another group reported a marmoset model of polyglutamine (polyQ) disease (Tomioka, Ishibashi, et al, 2017; Tomioka, Nogami, et al, 2017). The transgenic marmosets expressing functional reporter genes were generated by our own efforts and the summary of our work and ongoing progress will be discussed later in this review.…”
Section: Introductionmentioning
confidence: 99%
“…The transgenic marmosets expressing functional reporter genes were generated by our own efforts and the summary of our work and ongoing progress will be discussed later in this review. In an attempt to mimic inherited human neurodegenerative diseases, transgenic marmosets expressing the human ataxin 3 gene with expanded polyQ stretch were developed as a model of polyQ diseases (Tomioka, Ishibashi, et al, 2017). These transgenic marmosets demonstrated no neurological symptoms at birth, but showed slower growth curves, and gradual decreases in spontaneous activity and grip strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first transgenic primate showing successful germline transmission of transgenes was accomplished using the marmoset in which lentiviruses expressing enhanced green fluorescent protein (EGFP) were injected into preimplantation embryos (Sasaki et al 2009). A similar technology was also used to generate transgenic marmosets expressing genetically encoded calcium indicators ((Sasaki et al 2009; Park et al 2016; Tomioka et al 2017). Shortly after the reporting of the first genetically modified marmosets, the marmoset genome was sequenced and assembled using various strategies including Sanger sequencing at 6× coverage (Marmoset Genome Sequencing and Analysis Consortium 2014; Sato et al 2015).…”
Section: Introductionmentioning
confidence: 99%